Efficacy and safety of different treatments in chemotherapy-induced thrombocytopenia: a systematic review and network meta-analysis - Yang, Huiyan; Xu, Xiaoxiao; Tan, Mei; Gao, Jingyu; Fang, Ruihan; Liu, Xuan; Chen, Zhaokun; Chen, Libai; Ruan, Yongsheng; Xu, Yiqi; Luo, Yaxin; Wu, Xuedong (Frontiers in Pharmacology, 2025)
BackgroundChemotherapy-induced thrombocytopenia (CIT) is a challenge in cancer treatment, increasing bleeding risks and reducing chemotherapy dose. We sought to compare the efficacy and safety of various treatments for CIT.MethodsRandomized controlled trials (RCTs) involving CIT treatments were subjected to a systematic review and network meta-analysis. PubMed, Embase, Web of Science, Cochrane Library, and ClinicalTrials.gov databases were searched up to 2 July 2024.ResultsSixteen RCTs (n = 1,746) were included in this study. Pairwise meta-analysis showed thrombopoietic agents significantly reduced platelet transfusions (OR = 0.50; 95% CI: 0.32–0.77), improved nadir platelet count (SMD = 0.39; 95% CI: 0.25–0.53) and promoted platelet recovery ≥100 × 109/L (SMD = −0.48; 95% CI: −0.68 to −0.28). Thrombopoietin receptor agonists (TPO-RAs) reduced chemotherapy delays or dose reductions (OR = 0.37; 95% CI: 0.20–0.67) and the incidence of grade 3/4 thrombocytopenia (OR = 0.50; 95% CI: 0.27–0.93). Network meta-analysis indicated that eltrombopag ranked first in reducing chemotherapy dose reductions or delays and increasing nadir platelet count. In terms of reducing the incidence of grade 3/4 thrombocytopenia, recombinant human thrombopoietin (rhTPO) ranked highest, followed by eltrombopag. Recombinant human interleukin-11 (rhIL-11) had the lowest platelet transfusion rate but the highest incidence of adverse events, whereas avatrombopag had the lowest rate of adverse events and thromboembolism. Additionally, avatrombopag outperformed eltrombopag in promoting hemoglobin and neutrophils recovery.ConclusionThrombopoietic agents may benefit CIT patients. TPO-RAs, particularly eltrombopag, show superior efficacy and good tolerability. Although rhIL-11 and rhTPO can rapidly promote platelet recovery and reduce platelet transfusions, they have several limitations.Systematic Review Registration:https://inplasy.com/inplasy-2024-11.0105/